On-Off Control System for Temperature and Humidity in A Sweet Potato Chip Dryer using Heating Elements - Bobi Khoerun; Cahyono Putra; Rahajeng Kurnianingtyas (P3M Politeknik Negeri Banjarmasin, 2026)
Sweet potato chips are an innovative processed product that has been widely developed by Micro, Small, and Medium Enterprises in several regions. Most sweet potato chips are dried using traditional methods, such as direct sun drying. However, during the rainy season, solar heat cannot be used optimally, so the drying pro-cess tends to be slower. This study aims to create a temperature and humidity control system for a sweet potato chip drying machine using a dual air heater. Based on previous studies, temperature and humidity are crucial factors in food drying because they affect product quality. Earlier studies on drying ovens and temperature-controlled drying systems have shown that on-off control can maintain temperatures close to the setpoint with a simple design and low cost for small-scale applications. In addition, the development of microcontrollers such as the Arduino Uno has made it possible to design automatic control systems that can monitor and adjust temperature and humidity in real time. The method used in this study was the design of a laboratory-scale dry-ing oven equipped with a DHT22 sensor, an Arduino Uno, and an on-off control system using a heater and fan as actuators. System performance was evaluated under several operating conditions, namely with and without the control system. The results showed that the control system was able to maintain the dryer temperature with-in the range of 45°C to 55°C and relative humidity between 35% and 40%. In addition, increasing the drying time from 2 hours to 3 hours reduced the product moisture content from 39.9% to 7.7%.